PENGEMBANGAN MEDIA POWER POINT INTERAKTIF PADA PEMBELAJARAN NIHONGO SHOKYUU 1 BERBASIS VIRTUAL CLASSROOM - Adrian Hidayat Saputra; Hadriana Hadriana; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to describe the stages of development learning media in the form of interactive multimedia powerpoint based virtual classroom, describes the quality of learning media developed in the form interactive multimedia powerpoint and describe the validator and student responses on the use of learning media in the form of interactive multimedia powerpoint. This research is a development research (R&D) with ADDIE as the research method. Population This research is a Japanese language education student class of 2021, University of Riau. Determination sample using data analysis using a score of questionnaire sheet with a Likert scale that has been modified to 5 points. Based on this technique, obtained 37 students from batch 2021 as test subjects. Data collection technique using a questionnaire in the form of a questionnaire that must be filled in by the validator and students after presenting the material on the learning media. Before being tested, the media learning through the stages of media validation and material validation by media experts and material expert. Data analysis techniques using descriptive, namely by look for the percentage of answers on the questionnaire. The data obtained from the results Student response questionnaires are then calculated by adding up, averaging and looking for percentages to test the practicality of the product being used. developed.Keywords: Media, learning, powerpoint interactive, virtual classroom